A constituição subjetiva e saúde mental: contribuições winnicottianas - Cambuí, Heloisa Aguetoni; Neme, Carmen Maria Bueno; Abrão, Jorge Luís Ferreira (Programa de Pós-graduação em Teoria Psicanalítica do Instituto de Psicologia da Universidade Federal do Rio de Janeiro - UFRJ, 2016)
ABSTRACT Subjective constitution and mental health: Winnicott's contributions. Towards the emotional suffering observed in contemporary psychoanalytic practice, this article discusses the implications of initial inter-human relationships for the subjective constitution. Based on Winnicott's psychoanalytic references, the paper presents some reflections that contemplate the dimensions of mental health and illness from a relational psychopathological perspective. The psychic suffering discussed arises from possible traumatic experiences in the midst of the mother-infant relationship, which may lead the individual to a confusing experience, or even to the impossibility of gestating his/her own psychic birth. The conclusion is that the Winnicott's paradigm has contributed in an original way to the field of mental health, enabling differential clinical managements.

RESUMO Perante o sofrimento emocional observado na clínica psicanalítica contemporânea, pretende-se discutir as implicações das relações inter-humanas iniciais para a constituição subjetiva. Sob o referencial psicanalítico winnicottiano, apresentam-se reflexões que contemplam as dimensões de saúde psíquica e adoecimento a partir de uma perspectiva psicopatológica relacional. O sofrimento psíquico aqui referido se origina de possíveis experiências traumáticas no bojo da relação mãe-bebê, que podem levar o indivíduo a uma vivência confusa, ou, ainda, à impossibilidade de gestar seu próprio nascimento psíquico. Conclui-se que o paradigma winnicottiano contribuiu de forma original para o campo da saúde mental possibilitando manejos clínicos diferenciados.
Keywords: Mother-infant relationship; psychic constitution; Winnicott; psychic suffering; mental health; Relação mãe-bebê; constituição psíquica; Winnicott; sofrimento psíquico; saúde mental